Design and implementation of a new motorized-mechanical exoskeleton based on CGA Patternized Control - W. Banchadit (2018)
Exoskeleton is an active external mechanical structure attached to a part of human body to augment power or increase mobility of that body part. The exoskeleton is frequently used in military or rehabilitation purposes. In this study, we are focusing on the design and development of a novel mechanical design of the extremity lower-limb exoskeleton for the patients with spinal cord injury. The design is based on our lower-limb biomechanical analysis which a new concept of using a spring system for energy storage is employed in the designed exoskeleton to compensate the peak torques required at each joint. Our exoskeleton is consisting of 9 degree-of-freedoms covering the hip, knees and ankles. The introduced control algorithm for the exoskeleton is called 'Patternized Control Approach,' based on the Clinical Gait Analysis (CGA). A set of demonstrating results is shown, and is able to conclude a satisfactory performance of the system. © 2012 IEEE.